Sequências de tempos em completivas finitas: restrições lexicais e efeitos na aquisição - Gonçalves, Anabela (2013)
This paper is focused on the distribution of tenses in finite complement clauses in Portuguese. We first show that the concept of tense dependence does not explain all the restrictions to tenses in embedded clauses. Both temporal orientation and other semantic factors constrain the tenses that may occur in a complement clause. We also analyse tense sequences in a corpus of child spontaneous speech. In light of our previous analysis, we suggest an early restriction in child grammar: the sequences of tenses produced by the child in first stages may suggest avoidance of tense dependence.